2022
DOI: 10.1002/biot.202200237
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical time‐series analysis of dynamic bioprocess systems

Abstract: Background: Monoclonal antibodies (mAbs) are leading types of 'blockbuster' biotherapeutics worldwide; they have been successfully used to treat various cancers and chronic inflammatory and autoimmune diseases. Biotherapeutics process development and manufacturing are complicated due to lack of understanding the factors that impact cell productivity and product quality attributes. Understanding complex interactions between cells, media, and process parameters on the molecular level is essential to bring bioman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Follow-up studies could provide additional metabolic intermediates data for Raman base model calibration by using metabolomics methods such as 1 H-NMR [16]. When dealing with variable selection for the top BEM, process knowledge is required to include or exclude specific variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Follow-up studies could provide additional metabolic intermediates data for Raman base model calibration by using metabolomics methods such as 1 H-NMR [16]. When dealing with variable selection for the top BEM, process knowledge is required to include or exclude specific variables.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, BEM core model was developed to estimate the maturity of processes from the measured parameters and detect variations of parameters from their ideal trajectory [16]. To do this, the N × J × K (i.e.…”
Section: Bem Modelingmentioning
confidence: 99%
“…In the biopharmaceutical sector, living cells constitute the central platform for manufacturing a diverse array of pharmaceutical products known as biologics. [1,2] Chinese hamster ovary (CHO) cells are extensively employed as expression systems for the commercial production of monoclonal antibodies (mAbs). [3] Cultivated within chemically defined serum-free media, CHO cells rely on an array of essential components to drive cell growth, mAb expression, and the control of critical quality attributes (CQAs) like charge variants, glycosylation, and size variants.…”
Section: Introductionmentioning
confidence: 99%
“…1 H NMR has been applied for predicting the bioprocess performance, and for early identification of potential biochemical markers linked to cell starvation, viability, and expansion, to favor the timely control of culture conditions, through global multi‐component analysis [ 14–17 ] . These previous successful attempts have demonstrated that the 1 H NMR technology does have great application potential in the monitoring and control of bioprocesses [ 18,19 ] . 1 H NMR spectra could provide atomic‐level detail of small organic molecules in mixtures and give quantitative information in a highly reproducible way with very limited sample preparation.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] These previous successful attempts have demonstrated that the 1 H NMR technology does have great application potential in the monitoring and control of bioprocesses. [18,19] 1 H NMR spectra could provide atomic-level detail of small organic molecules in mixtures and give quantitative information in a highly reproducible way with very limited sample preparation.…”
Section: Introductionmentioning
confidence: 99%